Aspects of vaginal microbiota and the relationship with candidiasis in pregnant women: a literature review (Research, Society and Development, 2022)
The vaginal microbiota has an important role in the balance, maintenance and prevention of vaginal health in women, having a vast amount of microorganisms. Candida spp. it is one of the fungal species that most causes infections in humans. During pregnancy, when hormone levels are high and there is a variation in the vaginal pH, these microorganisms can colonize the vagina and consequently lead to an infection. This study aims to evaluate aspects of the vaginal microbiota and its correlation with vulvovaginal candidiasis in pregnancy, and its forms of diagnosis. The present study is characterized by being an integrative literature review, where the scientific platforms PubMed, Academic Google, Medline and Scielo Articles were used as data sources. The data generated in the research demonstrated the importance of understanding the vaginal microbiota. In addition to highlighting the importance of studies on vulvovaginal candidiasis in pregnant women, and how other Candida sp. are affecting and increasing the rates of patients with vaginal discharge, in addition to Candida albicans, which is the most studied species of this genus. Also note the relevance of the diagnosis of this disease. Thus, we conclude that knowledge of the clinical aspects of symptoms, especially during pregnancy, is an important tool for early diagnosis during the prenatal period. Vertical transmission is present in newborn infections. The most evident species of this genus is C. albicans, however, non-albicans Candida species are increasingly present in infections caused by the genus Candida spp.